REAL-LIFE READING: A SYSTEMATIC REVIEW - Wahdaniyah, Risma; Fadillah, Akbar Nabil; Andriana, Reva Putri; Tarihoran, Naf'an (Universitas Muria Kudus, 2025)
Real-life reading, which is defined as reading that takes place in regular situations outside of controlled environments, is examined in this systematic study. The study's objectives are to determine the variables affecting these behaviors, analyze the approaches taken, and point out areas that require more investigation. A thorough database search was carried out using PRISMA criteria and keywords like